Feasibility, Acceptability, and Preliminary Impact of Asdzáán Be'eená: An Intergenerational, Strength-Based, and Culturally Grounded Program to Improve the Health of Navajo Families. Issue 4 (October 2021) - Chambers, Rachel A.; Patel, Hima; Richards, Jennifer; Begay, Jaime; Littlepage, Shea; Begay, Marissa; Sheppard, Laurelle; Nelson, Danielle; Masten, Kristin; Mitchell, Kristin; Kee, Crystal; Barlow, Allison; et al.
Abstract : Native American youth endure a complex interplay of factors that portend greater risk-taking behaviors and contribute to marked health disparities experienced in adolescence. The Asdzáán Be'eená ("Female Pathways" in Navajo) program was developed as a primary prevention program to prevent substance use and teen pregnancy among Navajo girls. The Asdzáán Be'eená program consists of 11 lessons delivered to dyads of girls ages 8 to 11 years and their female caregivers. Feasibility, acceptability, and preliminary impact on risk and protective factors were assessed through a pre-/post study design. Data were collected from girls and their female caregivers at baseline, immediate, and 3 months postprogram completion. Forty-seven dyads enrolled in the study, and 36 completed the 3-month evaluation. At 3 months postprogram, girls reported significant increases in self-esteem, self-efficacy, parent-child relationship, social support, cultural, and sexual health knowledge. Caregivers reported increased family engagement in Navajo culture and parent-child communication and improved child functioning (fewer internalizing and externalizing behaviors). Findings suggest Asdzáán Be'eená has potential to break the cycle of substance use and teen pregnancy in Native communities by improving protective and reducing risk factors associated with these adverse health outcomes. Additional rigorous efficacy trials are necessary to establish program effectiveness.